A Randomized Controlled Simulation Trial of a Neonatal Resuscitation Digital Game Simulator for Labour and Delivery Room Staff - Christiane Bilodeau; Georg M. Schmölzer; Maria Cutumisu (MDPI AG, 2024)
Background: Healthcare providers (HCPs) working in labour and delivery rooms need to undergo regular refresher courses to maintain their neonatal resuscitation skills, which are shown to decline over time. However, due to their irregular schedules and limited time, HCPs encounter difficulties in readily accessing refresher programs. RETAIN is a digital game that simulates a delivery room to facilitate neonatal resuscitation training for HCPs. Objective: This study aims to ascertain whether participants enjoyed the RETAIN digital game simulator and whether it was at least as good as a video lecture at refreshing and maintaining participants' neonatal resuscitation knowledge. Methods: In this randomized controlled simulation trial, n = 42 labour and delivery room HCPs were administered a pre-test of neonatal resuscitation knowledge using a manikin. Then, they were randomly assigned to a control or a treatment group. For 20-30 min, participants in the control group watched a neonatal resuscitation lecture video, while those in the treatment group played the RETAIN digital game simulator of neonatal resuscitation scenarios. Then, all participants were administered a post-test identical to the pre-test. Additionally, participants in the treatment group completed a survey of attitudes toward the RETAIN simulator that provided a measure of enjoyment of the RETAIN game simulator. After two months, participants were administered another post-test identical to the pre-test. Results: For the primary outcome (neonatal resuscitation performance), an analysis of variance revealed that participants significantly improved their neonatal resuscitation performance over the first two time points, with a significant decline to the third time point, the same pattern of results across conditions, and no differences between conditions. For the secondary outcome (attitudes toward RETAIN), participants in the treatment condition also reported favourable attitudes toward RETAIN. Conclusions: Labour and delivery room healthcare providers in both groups (RETAIN simulator or video lecture) significantly improved their neonatal resuscitation performance immediately following the intervention, with no group differences. The findings suggest that participants enjoyed interacting with the RETAIN digital game simulator, which provided a similar boost in performance right after use to the more traditional intervention.